In Situ Characterization of Interfaces Relevant for Efficient Photoinduced Reactions. Issue 21 (10th October 2017) - Supplie, Oliver; May, Matthias M.; Brückner, Sebastian; Brezhneva, Nadzeya; Hannappel, Thomas; Skorb, Ekaterina V.
Abstract: Solar energy conversion and photoinduced bioactive sensors are representing topical scientific fields, where interfaces play a decisive role for efficient applications. The key to specifically tune these interfaces is a precise knowledge of interfacial structures and their formation on the microscopic, preferably atomic scale. Gaining thorough insight into interfacial reactions, however, is particularly challenging in relevant complex chemical environment. This review introduces a spectrum of material systems with corresponding interfaces significant for efficient applications in energy conversion and sensor technologies. It highlights appropriate analysis techniques capable of monitoring critical physicochemical reactions in situ during non‐vacuum preparation and photoactivity studies including well‐defined inorganic epitaxial reference surfaces, buried interfaces, and low‐defect nucleation of disjunct epitaxial materials that are analyzed during preparation in chemical vapor environment. Their surfaces are then modified and functionalized in gaseous and liquid environment. Finally, even more complex coupling of inorganic stable photoactive materials with responsive soft matter for bioactivity is reviewed. Interface formation, structure, and/or artificial photochemical interfacial reactions are scrutinized down to the atomic scale in real time, also accounting for equilibrium versus non‐equilibrium, kinetically driven processes, in order to accelerate progresses in the realization of efficient energy materials and in the exploitation of photoinduced processes at interfaces. Abstract : Interfaces play a decisive role in efficient solar energy conversion and photoactive sensors. Gaining thorough insight into interfacial reactions, however, is particularly challenging in relevant complex, non‐vacuum environments. This review focuses on in situ studies of interface formation during preparation in chemical vapor ambient, modification in gaseous and liquid environment, and coupling of inorganic photoactive material with bioactive soft matter.